180k views
5 votes
Find the derivative of function y=4x^2-9x-6 using the limiting process . Show your work including: difference quotient , steps to simplify, how you set up the limit , and the derivative

1 Answer

1 vote

By the definition of the derivative,


f'(x)=\displaystyle\lim_(h\to0)\frac{f(x+h)-f(x)}h


\implies y'=\displaystyle\lim_(h\to0)\frac{(4(x+h)^2-9(x+h)-6)-(4x^2-9x-6)}h

Simplify the numerator:


4(x+h)^2-9(x+h)-6=4(x^2+2xh+h^2)-9(x+h)-6


=4x^2+8xh+4h^2-9x-9h-6

Subtracting
4x^2-9x-6 removes all the terms here not involving
h, so the limit reduces to


y'=\displaystyle\lim_(h\to0)\frac{8xh+4h^2-9h}h

Cancel the factor
h in the numerator and denominator:


y'=\displaystyle\lim_(h\to0)(8x+4h-9)

As
h\to0, we're left with


\boxed{y'=8x-9}

User Matthew Schuchard
by
5.8k points